Consistent higher derivative quantum field theory: A model without tachyons and ghosts - Dutra, Alvaro de Souza [UNESP]; Natividade, C. P. [UNESP] (World Scientific Publishing, 1996)
We present a higher derivative gauge theory in (2 + 1) dimensions which can have its parameters suitably tuned in order to become a consistent quantum field theory, in the sense that both tachyons and ghosts are absent from the particle spectrum of the theory.